PENGEMBANGAN PERDAGANGAN KECIL DAN MENENGAH DI KOTA SEMARANG (STUDI KASUS PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI JAWA TENGAH DI BIDANG PERDAGANGAN) - Inki Megawati Kintani; Michelin Astrifence Munte (JOURNAL EQUITABLE, 2024)
This study discusses how the performance of programs implemented by the Industry and Trade Office of Central Java Province related to the development of small and medium trade in Semarang City. The program is designed to address the problems of MSMEs in Semarang. In this study using research design, namely descriptive qualitative research methods. The source of this research data was obtained through two sources, namely primary data and secondary data where primary data was obtained by making observations. Conclusion this research is an effort to develop small and medium trade (MSMEs) in Semarang City, programs carried out by the Industry and Trade Office of Central Java Province have contributed to overcoming problems faced by MSMEs, such as marketing, capital, and human resources